KORELASI ANTARA USIA,INDEKS MASSA TUBUH (IMT), KADAR GULA DARAH PUASAPADA KOMUNITAS VEGETARIAN DEWASA DI KOTA PEKANBARU - Annajmi "; Suyanto "; Fatmawati " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Vegetarian diet has many benefits, especially in the field of health, suchas, lowering the risk for diabetes mellitus and obesity. Research has also shownthat vegetarians have a body mass index lower than non-vegetarians. However,high carbohydrate consumption, and several types of vegetarians who stillconsume milk in excessive amounts, can contribute to blood glucose levels. Thisdiet can affect nutritional status too. In addition, age can also affect nutritionalstatus, by increasing of age, the body composition will be changed and metabolicrate will be decreased. This study was aimed to determine the correlation betweenage, BMI , and fasting blood glucose levels in adult vegetarian community inPekanbaru . This is a correlative study with cross sectional design. The dataincluded the age, type and duration of being a vegetarian, BMI, and fasting bloodglucoselevels . The samples were taken by purposive sampling technique with 32people who met the inclusions criteria. The results of this study indicate that therewere no different of BMI (p= 0.734), and fasting blood glucose levels ( p = 0.804)between vegans and non - vegans .This study also showed that there was nosignificant correlation between age and fasting blood glucose levels in adultvegetarian community (r= 0,075; p=0,682). In addition , the results showed thatthere was no significant correlation between BMI and fasting blood glucose levels(p=0.414; r=0.149 ) in the adult vegetarian community. There was no significantcorrelation between BMI and fasting blood sugar levels in the vegan group(p=0.793; r= -0.207 ) and the non- vegan (p=0.394; r=0.184) in adult vegetariancommunity in Pekanbaru .Key words :Vegetarian,Vegan, Non-vegan, Body Mass Index (BMI), FastingBloodGlucose Levels